Primary Repair of Traumatic Gut Injury Without Diversion in Casualty Department of Dhaka Medical College Hospital (Faridpur Medical College Journal, 2014)
Colon is one of the most commonly injured viscera followed by small gut and liver in abdomen for which management becomes complicated had the type and severity of injury not been assessed properly. With improved facilities in patient care and proper use of antibiotics the inclination is directed towards primary repair of colon without diversion. This study was aimed to assess the efficacy of primary repair in a tertiary hospital. A number of 50 patients of traumatic gut injury from 15-50 years (31.18 ± 9.38 years) mainly presenting with RTA with blunt trauma abdomen (54.0%) and different types of stab injury (40.0%) were managed with primary repair in the department of casualty in Dhaka Medical College Hospital, Dhaka between the period of January to June 2009. On admission more than half (52.0%) had hypotension, 70.0% distended abdomen, 84.0% tender abdomen, 58.0% presented with abdominal rigidity while 80% of them had perforation of the small and 20% had the same in large gut. After primary repair, only 6% developed chest infection and 4% developed wound infection. The findings suggest that primary repair without diversion in the treatment of traumatic gut injury can be performed among patients admitted in our hospitals. DOI: http://dx.doi.org/10.3329/fmcj.v8i2.20390 Faridpur Med. Coll. J. 2013;8(2): 77-79